Renal function impairment in Hypothyroidism (Bangladesh Journal of Medical Biochemistry, 2013)
Background: Hypothyroidism is an important public health problem in Bangladesh. It is associated with increased risk for atherosclerosis and other complications. The frank development of hypothyroidism is associated with metabolic derangements including dyslipidemia- which is an etiopathologic factor for development of renal impairment. This study was to evaluate whether hypothyroidism is associated with impaired renal function. Methods: Using a cross sectional analytical study design, a total of 111 subjects attending Out Patient Department, Center for Nuclear Medicine and Ultrasound, Bogra Medical College during January 2007 to December 2007 were included purposively. Eighty newly diagnosed hypothyroid patients (Group I) and 31 healthy adults (Group II) were enrolled in this study. Serum thyroid stimulating hormone and serum free thyroxine were assayed by radioimmunoassay. Serum fasting lipid profile, serum creatinine and serum uric acid were estimated by enzymatic colorimetric method. Estimated GFR was calculated using MDRD equation. Results: The mean (±SD) age of in Group I and Group II were 35.59 (±6.91) and 37.35 (±2.78) years and were comparable. In Group I, there were 66 females and 14 males. In Group II, there were 16 females and 15 males. The mean BMI was 25.49 ±2.17 kg/m2 in Group I and 24.24 ±1.99 kg/m2 in Group II. The mean (±SD) Serum total-cholesterol, LDL- cholesterol and tryacylglycerol in Group I were significantly higher than that in Group II. Serum HDL cholesterol in Group I was significantly lower than that in Group II (p